The Association of Asian Veterinary Schools: making a difference in veterinary education - Saad, Mohd Zamri (Universiti Putra Malaysia Press, 2004)
The Association of Asian Veterinary School (AAVS) is a ‘new’ association, which was formed to enhance the advancement of veterinary education and research in Asia. It can be used by member and non-member institutions as a platform to start collaboration in education and research in veterinary medicine in Asia. Through the Executive Committee and the three sub-committees, activities associated with education and research can be initiated. Like many other associations, inactivity of AAVS may arise due to lack of recognition, financial support and commitment from members.